ELaPro, a LOINC-mapped core dataset for top laboratory procedures of eligibility screening for clinical trials - Rafee, Ahmed; Riepenhausen, Sarah; Neuhaus, Philipp; Meidt, Alexandra; Dugas, Martin; Varghese, Julian (BMC medical research methodology, 2022)
Screening for eligible patients continues to pose a great challenge for many clinical trials. This has led to a rapidly growing interest in standardizing computable representations of eligibility criteria (EC) in order to develop tools that leverage data from electronic health record (EHR) systems. Although laboratory procedures (LP) represent a common entity of EC that is readily available and retrievable from EHR systems, there is a lack of interoperable data models for this entity of EC. A public, specialized data model that utilizes international, widely-adopted terminology for LP, e.g. Logical Observation Identifiers Names and Codes (LOINC®), is much needed to support automated screening tools.
Gesehen am 15.06.2022